2007
DOI: 10.1016/j.jbiomech.2007.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Detection of trabecular bone microdamage by micro-computed tomography

Abstract: Microdamage is an important component of bone quality and affects bone remodeling. Improved techniques to assess microdamage without the need for histological sectioning would provide insight into the role of microdamage in trabecular bone strength by allowing the spatial distribution of damage within the trabecular microstructure to be measured. Nineteen cylindrical trabecular bone specimens were prepared and assigned to two groups. The specimens in group I were damaged to 3% compressive strain and labeled wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 19 publications
4
53
0
Order By: Relevance
“…Proposed screening modalities include plain X-ray, computed tomography, magnetic resonance imaging (MRI), and isotope bone scanning [7,8]. Taking into account the suggested mechanisms of bisphosphonate associated fracture, one might also theorise a role for micro-computed tomography [9,10], positron emission tomography [11] or possibly bone turnover markers.…”
Section: Discussionmentioning
confidence: 99%
“…Proposed screening modalities include plain X-ray, computed tomography, magnetic resonance imaging (MRI), and isotope bone scanning [7,8]. Taking into account the suggested mechanisms of bisphosphonate associated fracture, one might also theorise a role for micro-computed tomography [9,10], positron emission tomography [11] or possibly bone turnover markers.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that even loads below the ultimate bone stress can cause bone failure, as in the case of fatigue failures, in which the microdamage of bone can no longer be repaired [18]. The accumulated microdamage might result in bone resorption.…”
Section: Implant Design and Stress Of Jaw Bonementioning
confidence: 99%
“…Bony microstructure also has been assessed in animal studies by micro-CT (high-resolution peripheral quantitative computed tomography) [10,52,53]. Micro-CT has become increasingly popular for in vivo assessment of osteoporosis in human bone [8,9], and we presumed it could be used similarly with porous tantalum.…”
Section: Introductionmentioning
confidence: 99%